1977
DOI: 10.1071/mf9770439
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the ecology of some temporary freshwater pools in Victoria with special reference to microcrustaceans

Abstract: Fifty-three temporary freshwater pools (mean depth 23 cm) located mainly in eastern Victoria were studied from February to September 1973. Chemical parameters determined were pH (range 5.7-8.2, mean 6.9), conductivity (K18, range 55-5500, mean 340 �S/cm), dissolved oxygen (range 23-170, mean 72% saturation) and turbidity (range 2-310, mean 50 Formazin turbidity units). A total of 60 microcrustacean species was recorded. The Australasian endemic cladoceran, Saycia cooki (King), was of common occurrence from Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 20 publications
4
27
1
Order By: Relevance
“…The conductivities of the ponds at Ohau and Tekapo were low compared with those of temporary freshwater ponds in southeast Australia (Morton & Bayly 1977) and southwest Australia (Bayly 1982), but were near the low end of the range of conductivities reported by Stout (1975) for Canterbury high-country lakes. Sodium and chloride contributed proportionally more to the total salinity than is characteristic of fresh waters of the same conductivity on continents (Hutchinson 1957).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The conductivities of the ponds at Ohau and Tekapo were low compared with those of temporary freshwater ponds in southeast Australia (Morton & Bayly 1977) and southwest Australia (Bayly 1982), but were near the low end of the range of conductivities reported by Stout (1975) for Canterbury high-country lakes. Sodium and chloride contributed proportionally more to the total salinity than is characteristic of fresh waters of the same conductivity on continents (Hutchinson 1957).…”
Section: Discussionmentioning
confidence: 92%
“…In their study of 53 temporary pools in southeast Australia, Morton & Bayly (1977) noted that D. carinata and Simocephalus exspinosus never cooccurred and suggested that this may imply that if these 2 species are brought together in shallow pools only 1 is capable of survival. Although we found that these 2 species generally did not co-occur, we recorded them together in Pond 20 at Ohau.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B. major Searle matures rapidly, typically within a few weeks after a wetland fills, produces resting eggs and then disappears (Green et al 1999). B. pseudochelae Searle reaches maximum numbers later, more towards the middle of a pool's hydroperiod (Morton and Bayly 1977). At this stage more information is needed to determine the life-history of B. pilkililli.…”
Section: General Features and Life-histories Of Calanoidsmentioning
confidence: 99%